How a Cerebral Hemorrhage Altered My Art - Sherwood, Katherine D. (Frontiers in Human Neuroscience, 2012)
“How a Cerebral Hemorrhage Altered My Art” examines how a massive stroke affected my art practice. The paralysis that ensued forced me to switch hands and become a left-handed painter. It was postulated by several neuroscientists that the “interpreter” in my brain was severely damaged during my CVA. This has had a profoundly liberating effect on my work. Whereas my pre-stroke period had the tendency to be over-intellectualized and forced, my post-stroke art is less self-conscious, more urgent and expressive. The primary subject matter of both periods is the brain. In my practice as an artist, my stroke is a challenge and an opportunity rather than a loss.